2018
DOI: 10.1111/ans.14836
|View full text |Cite
|
Sign up to set email alerts
|

Point‐of‐care viscoelastic assay devices (rotational thromboelastometry and thromboelastography): a primer for surgeons

Abstract: Background: Bleeding is a common occurrence in surgery. Point-of-care testing with viscoelastic (VE) assays such as thromboelastography (TEG) and rotational thromboelastometry (ROTEM) has become more common place. TEG and ROTEM have the potential to guide management of coagulopathy. Many healthcare professionals still rely upon standard laboratory tests (SLTs) to manage a bleeding patient. It was our aim to investigate the literature surrounding management of the surgically bleeding patient via VE assays. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
(148 reference statements)
0
5
0
1
Order By: Relevance
“…The VCM Vet analyzer could serve as a bedside test for the global assessment of coagulation in veterinary patients presenting with an array of hemostatic abnormalities. In human patients, one of the largest uses of viscoelastic tests is hemostasis monitoring in hypocoagulable patients requiring blood product transfusions secondary to trauma or invasive surgical procedures 9,10,11,12 . Viscoelastic tests in these patient populations have resulted in the use of fewer blood products and associated adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The VCM Vet analyzer could serve as a bedside test for the global assessment of coagulation in veterinary patients presenting with an array of hemostatic abnormalities. In human patients, one of the largest uses of viscoelastic tests is hemostasis monitoring in hypocoagulable patients requiring blood product transfusions secondary to trauma or invasive surgical procedures 9,10,11,12 . Viscoelastic tests in these patient populations have resulted in the use of fewer blood products and associated adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Study results from trauma[ 7 ], liver transplant[ 8 ] and cardiac surgeries[ 9 ] have shown that the goal-directed allogeneic transfusion strategy is believed to provide better hemostatic competence. This was possibly due to the more timely administration of blood products such as plasma and platelets, which in turn resulted in less blood loss[ 3 ], reduced blood transfusion needs[ 10 ], lower costs, and fewer adverse events[ 11 ] in the TEG-guided transfusion group than in the conventional transfusion group. One study also suggested that TEG-guided transfusion could substantially affect patient outcomes, including length of hospital stay, odds of reoperation, and short-term mortality[ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A viscoelastic assay (VEA), by either thromboelastography (TEG) ( Figure 4 ) or rotational thromboelastometry (ROTEM), assesses several parameters of fibrin formation and HF and/or FS in whole blood [ 165 , 166 , 167 , 168 ]. VEA-based assessment of coagulation provides a rapid, integrated measure of clot formation and dissolution in blood compared to conventional coagulation tests (CCT) of individual coagulation pathways performed on prepared plasma and therefore in the absence of platelets and red cells.…”
Section: Management Of the Polytrauma Victimmentioning
confidence: 99%